Analysis of the Application of E-Commerce Applications in Increasing Sales Revenue at PT. United Tractors Tbk. Alvin Krisdian, Shela, Jenifen, Juliani, Financial Management Study Program, Faculty of Economics Prima University of Indonesia - Alvin Krisdian; Jenifen; Shela; Rafida Khairani (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to understand the income before and after implementing the e-commerce system at PT. United Tractors Tbk. the type of research is